The Role of Personality in Daily Food Allergy Experiences - Conner, Tamlin S.; Mirosa, Miranda; Bremer, Phil; Peniamina, Rana (Frontiers in Psychology, 2018)
Food allergies present numerous challenges to coping in everyday life. Even simple things like planning a lunch with a friend can be stressful for people with food allergies. But are some people more adversely impacted by having a food allergy than other people? This paper addressed this question by investigating whether individual differences in the Big Five personality traits (neuroticism, extraversion, openness, agreeableness, and conscientiousness) are related to food allergy-related problems in everyday life among adults with food allergies. Participants were 108 adults [85% female; mean age = 40.2; age range 18 to 87] with a physician-diagnosed food allergy [most commonly to gluten (54.6%), peanuts (21.3%), cow’s milk (16.7%), and shellfish/seafood (16.7%)]. Participants completed an initial online survey that measured demographics, food allergy information, and personality traits using the Big Five Inventory (John, Donahue, & Kentle, 1991). For two weeks, participants completed a daily online survey that queried the occurrence of 25 food allergy issues that day and participants’ overall stress and mood that day. Neuroticism did not predict more frequent allergy issues or greater stress / poorer mood on days with more allergy issues. Instead, higher openness to experience predicted a range of issues including going hungry because there is no safe food available, problems finding suitable foods when grocery shopping, feeling anxious at social occasions involving food, being excluded, and feeling embarrassed and poorly understood about their food allergy. Conscientious people were less embarrassed or self-conscious about their food allergy, but they had more problems eating out, and their positive mood was more impaired by allergy issues than their less conscientious peers. Extraversion and agreeableness played minor roles. Personality testing can identify people that may have difficulty living with food allergies – such as those higher in openness to experience.